(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article thoroughly investigates the intricate tapestry of cryptographic mechanisms and narrative strategies that converge in Dan Brown’s literary canon, illustrating how polyalphabetic ciphers, steganographic devices, and algorithmic techniques collectively augment thematic depth. By systematically analyzing textual references through computational, hermeneutic, and interdisciplinary comparative frameworks, the study elucidates the ways in which encoded elements elevate narrative tension, destabilize interpretive certainties, and engender a multilayered reading experience.